Listeria monocytogenes bacteremia one month after contact with raw venison: A case report. (2022) - Takahashi, Hidenori; Yokozawa, Takayuki; Oda, Toshimi
Abstract: Listeria monocytogenes is a gram-positive bacillus that causes food poisoning. Listeriosis causes gastrointestinal infections and occasionally leads to fatal bacteremia in older adults. The symptoms of Listeria infections are non-specific and difficult to diagnose. We describe a case of Listeria bacteremia in an 82-year-old Japanese woman who had handled raw venison one month prior to becoming ill, but had not consumed any. No other possible sources of infection were identified. She presented with a fever without any focal symptoms. Computed tomography revealed enteritis with mucosal damage. Blood culture revealed bacteria with gram-positive rod morphology, that were confirmed as L. monocytogenes using mass spectrometry. The patient was treated with intravenous ampicillin and made a full recovery. This case illustrates the virulence of L. monocytogenes, which can cause bacteremia from handling contaminated food, even without consumption. Highlights: An older woman presented with fever of unknown origin, without focal symptoms. Computed tomography revealed asymptomatic enteritis, with mucosal damage. Blood culture grew Listeria monocytogenes, confirmed by mass spectrometry. The most likely source of infection was handling raw venison one month previously. This case illustrates the virulence and delayed onset of Listeria infection.